2020
DOI: 10.1515/znb-2020-0024
|View full text |Cite
|
Sign up to set email alerts
|

The symmetry principle of antiaromaticity

Abstract: Aromaticity is one of the most widely used chemical concepts. Current definitions are purely phenomenological and relate symmetry, reactive stability and the occurrence of molecular diamagnetic response currents. The antithetical concept of antiaromaticity provides a connection between the contrary properties: structural instability or distortion out of higher symmetry, a small HOMO-LUMO gap, and paramagnetic response currents. We reveal the principle that is underlying antiaromaticity by showing an intimate a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…13,14 Notice that antiaromaticity and its prototypical paramagnetic response has been discussed as being intimately related to the symmetry of the system. 35 Additionally, the ring-current strengths of strongly antiaromatic molecules tend to be overestimated when functionals with none or little Hartree-Fock exchange are employed. A better agreement, with values obtained at the MP2 level, is achieved when the functional includes at least 50% of Hartree-Fock exchange.…”
Section: Cyclobutadienementioning
confidence: 99%
“…13,14 Notice that antiaromaticity and its prototypical paramagnetic response has been discussed as being intimately related to the symmetry of the system. 35 Additionally, the ring-current strengths of strongly antiaromatic molecules tend to be overestimated when functionals with none or little Hartree-Fock exchange are employed. A better agreement, with values obtained at the MP2 level, is achieved when the functional includes at least 50% of Hartree-Fock exchange.…”
Section: Cyclobutadienementioning
confidence: 99%
“…1 It has been the subject of numerous experimental and theoretical studies; a comprehensive account of pre-2012 research has been provided by Schleyer and co-workers. 1 The ground-state (S 0 ) potential energy surface (PES) of COT has been examined in considerable detail [2][3][4][5][6][7][8] and has been found to include symmetryequivalent tub-shaped local minima of D 2d symmetry connected through planar tub-to-tub ring-inversion transition states (TS) of D 4h symmetry; these, in turn, are connected through a planar p-bond-shifting TS in the form of a regular octagon of D 8h symmetry. In its electronic ground state D 8h COT is a singlet diradical and its full-symmetry description requires at least a two-determinant wavefunction; the attempt to use the standard single closed-shell Slater determinant results in a ''broken-symmetry'' wavefunction which suggests energetically favourable distortions of the nuclear framework to one of the two bond-alternating D 4h geometries.…”
Section: Introductionmentioning
confidence: 99%
“…In its electronic ground state D 8h COT is a singlet diradical and its full-symmetry description requires at least a two-determinant wavefunction; the attempt to use the standard single closed-shell Slater determinant results in a ''broken-symmetry'' wavefunction which suggests energetically favourable distortions of the nuclear framework to one of the two bond-alternating D 4h geometries. As shown by Hrovat and Borden, 3 the ground-state PES of COT can be described with high accuracy using a complete active-space self-consistent field (CASSCF) wavefunction with ''8 electrons in 8 orbitals'', CASSCF (8,8), accounting for the eight electrons involved in the bond rearrangements linking the D 2d , D 4h and D 8h stationary points; CASSCF (8,8) wavefunctions have been also found to work well in studies of several low-lying electronic states of COT. 4,6,9,10 Hu ¨ckel molecular orbital (HMO) theory depicts the ground electronic state of D 8h COT as an antiaromatic triplet which is incorrect in more than one way: Firstly, at this geometry COT has an antiaromatic singlet ground electronic state which violates Hund's rule and secondly, the lowest triplet state (T 1 ) of D 8h COT has been shown to be aromatic.…”
Section: Introductionmentioning
confidence: 99%
“…Antiaromaticity, defined as the co-existence of a paratropic ring current, symmetry breaking or structural distortion, and a small Fermi gap 168,169 can be understood in terms of a general underlying symmetry principle as pointed out by Berger and Viel: 170 170 SPA can also be applied to closed-shell states that are nondegenerate but nearly two-fold-degenerate. The magnetically induced paratropic ring current then appears together with a symmetry-induced (second-order) pseudo Jahn-Teller distortion, Q.…”
Section: Antiaromaticitymentioning
confidence: 99%
“…Berger and Viel suggested that antiaromaticity can be defined via the SPA as the presence of such a balance. 170…”
Section: Antiaromaticitymentioning
confidence: 99%